Assessments of propulsion models for free running surface ship turning circle simulations. (15th April 2022) - Yu, Jiawei; Feng, Dakui; Liu, Liwei; Yao, Chaobang; Wang, Xianzhou
Abstract: Two propeller models of RANS tools for ship maneuvering predictions are recommended by ITTC committee: discretized propeller model and body force model. In this paper, discretized propeller model and three different body force models are selected to conduct the ship turning circle maneuvering simulations. The direct URANS (unsteady Reynolds-averaged Navier–Stokes) CFD (computational fluid dynamics) method is adopted to assess ship turning circle performance of the self-propelled KCS (KRISO Container Ship) with KP505 propeller model and rudder. Rudder deflection and propeller rotation are executed by the application of hierarchy of overset grids while the ship undertakes 6 DOF dynamic motions. According to the benchmark case, KCS 35 ° turning circle test is simulated at F r = 0.26 using four propulsion models (including the discretized propeller model (DPM), descriptive body-force method (DBM), OUM (Osaka University Method) and modified OUM (MOUM) body-force methods). The present numerical method for maneuvering simulations is verified and validated by conducting the uncertainty analyses. The ship turning circle computational results have been compared against experimental data from literature and with each other in detail. It is found that DPM is able to predict ship turning circle performance well. The difference between DPM and body-force approach become noticeable when the drift angle is larger than 10 deg. DBM is shown to under-predict the magnitude of propeller induced wake passing the rudder and over-predict the tactical diameter, which is consistent with the literatures. The iterative body forces (OUM and MOUM) are found to solve this problem better, especially, MOUM shows higher accuracy in predicting the turning circle characteristics. Highlights: The ability of different propulsion models to predict ship maneuvering are compared comprehensively. The reasons for the differences in predicting ship turning performance using different propulsion models are analyzed. The computational efficiency of discretized propeller model and body force models are compared. The effects of the drift angle on ship turning prediction using body force models are discussed.